The organization of the curriculum and professional training of 2009 graduates from the faculty of education of the Jorge Basadre Grohmann National University in Tacna. - Choque Ticona, Nayme Antonieta (2015)
Objective: Determine the influence of the level of organization of the curriculum at the level of vocational training of graduates in 2009 from the Faculty of Education at the Jorge Basadre Grohmann National University of Tacna. Method: A descriptive research that establishes the level of curricular organization and its influence on the level of professional training. The sample consisted of 62 graduates in 2009 from the Faculty of Education at the Jorge Basadre Grohmann National University of Tacna. The data collection was conducted in late 2013 and early 2014. Two instruments were developed: a questionnaire to the graduates of 2009, and a data-analysis to establish the level of organization of the curriculum. Result: The results of the research allowed to establish that the organization of the curriculum is inadequate and the level of training is regular. These results allowed to establish direct and significant relationship between the level of organization of the curriculum and the level of training of graduates in 2009 from the Faculty of Education at the Jorge Basadre Grohmann National University of Tacna. Conclusions: The training received in the Faculty of Education at the National University Jorge Basadre Grohmann, is regulated according to the perception of the graduates, which is evidenced by the results of the opinion poll applied to graduates of 2009.